Pengembangan E-Modul Berbasis Deep Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Dan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi - Sri Karina Br Sebayang; Arwansyah Arwansyah; Sri Mutmainnah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research aims to develop a deep learning-based e-module and assess its feasibility as teaching material for Economics for Grade XI at MAN Karo. This research is motivated by students' low critical thinking skills and low learning outcomes, particularly in monetary and fiscal policy. This study uses the R&D method, assisted by the ADDIE model, which has the syntax of Analysis, Design, Development, Implementation, and Evaluation. The subjects were grades 11-4 and 11-5 students at MAN Karo in the 2025/2026 academic year. Data were collected through validation by material experts, media experts, and instructional design experts, as well as product trials through one-on-one trials, small group trials, and large group trials. The results of this study indicate that the Deep Learning-based e-module is highly feasible. Validation by material experts yielded a score of 81%, categorized as very feasible; validation by media experts yielded a score of 83%, categorized as very feasible; and validation by design experts yielded a score of 87%, categorized as very feasible. The product trial results for one-on-one testing showed a percentage of 83%, categorized as very feasible; small group testing showed a percentage of 80%, categorized as feasible; and large group testing yielded a percentage of 89.5%, categorized as very feasible. Overall, the average e-module feasibility percentage reached 83.9%, categorized as very feasible. These findings indicate that the developed e-module meets the feasibility criteria in terms of content, media, and design and supports interactive, student-centered learning in economics.